Die perioperative Handhabung von Antikoagulantien in der elektiven Handchirurgie - eine Literaturübersicht = Perioperative anticoagulation in elective hand surgery : a literature review - Ahrens, Carsten; Unglaub, Frank (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2016)
This review highlights pathways regarding the handling of anticoagulation in elective hand surgery based on current literature.
Gesehen am 09.12.2019